KUALITAS LAYANAN DAN DAMPAKNYA TERHADAP LOYALITAS PELANGGAN: STUDI MEDIASI KEPUASAN PELANGGAN - Mulyadi, Made; Sadwistri Adhityasari, Ni Made; Elvina Adi Saputri, Luh Gede; Arniti, Ketut (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
There is currently high interest in care or beauty because beauty care has become a need that is considered important for some people, especially women. This makes the care and beauty industry a profitable one in Indonesia. One service business that offers care and beauty in Bali is Yucan Salon. Yucan Salon strives to understand customer needs and desires in terms of fulfilling needs and comfort by providing various facilities and various quality services with the ultimate goal of customer satisfaction and customer loyalty after using Yucan Salon services. The aim of this research is to determine the effect of service quality on customer loyalty through customer satisfaction. The type of data used in this research is quantitative data by distributing questionnaires using Google Forms to 100 Yucan Salon customers who were the samples in this research. The analysis method used is PLS. The research results show that service quality has a positive effect on customer loyalty, service quality has a positive effect on customer satisfaction, customer satisfaction has a positive effect on customer loyalty, and service quality has an indirect positive effect on customer loyalty through customer satisfaction.